Coordination of inter-organelle communication and lipid fluxes by OSBP-related proteins. (April 2022) - Arora, Amita; Taskinen, Juuso H.; Olkkonen, Vesa M.
Abstract: Oxysterol-binding protein (OSBP) and OSBP-related proteins (ORPs) constitute one of the largest families of lipid-binding/transfer proteins (LTPs) in eukaryotes. The current view is that many of them mediate inter-organelle lipid transfer over membrane contact sites (MCS). The transfer occurs in several cases in a 'counter-current' fashion: A lipid such as cholesterol or phosphatidylserine (PS) is transferred against its concentration gradient driven by transport of a phosphoinositide in the opposite direction. In this way ORPs are envisioned to maintain the distinct organelle lipid compositions, with impacts on multiple organelle functions. However, the functions of ORPs extend beyond lipid homeostasis to regulation of processes such as cell survival, proliferation and migration. Important expanding areas of mammalian ORP research include their roles in viral and bacterial infections, cancers, and neuronal function. The yeast OSBP homologue (Osh) proteins execute multifaceted functions in sterol and glycerophospholipid homeostasis, post-Golgi vesicle transport, phosphatidylinositol-4-phosphate, sphingolipid and target of rapamycin (TOR) signalling, and cell cycle control. These observations identify ORPs as lipid transporters and coordinators of signals with an unforeseen variety of cellular processes. Understanding their activities not only enlightens the biology of the living cell but also allows their employment as targets of new therapeutic approaches for disease.